CT-based post-implant dosimetry for I-125 prostate brachytherapy: a multi-centre audit in the UK and Ireland. Issue 4 (22nd April 2013) - Hayman, O.; Palmer, A.
Abstract: Background and purpose: To assess the reliability of post-implant CT (PICT) dosimetry for I-125 prostate seed brachytherapy by investigating the variation between centres in performing PICT through a multi-centre audit. Materials and methods: Computerised tomography data sets from four I-125 prostate brachytherapy patients were circulated to nine participating centres. Centres followed local protocol for PICT outlining and seed identification, dosimetry for D90, V100 and V150 for the prostate was reported. Outlines were compared to determine the variation in: quality parameters (D90, V100 and V150), dose-volume histograms and approach to PICT dosimetry between the centres. Results: There was significant variation in the prostate outlines drawn by the nine centres; for a prostate with mean volume 43 cm 3, the range was 39–57 cm 3 which led to variations of D90 of 119–154 Gy (mean 140 Gy) and V100 of 80–93% (mean of 88%). Using automatic seedfinder software reduced discrepancies between centres identifying seeds; overall consistency in seed location was good. Conclusions: There was a significant uncertainty in the outlining of the prostate volume for PICT dosimetry with an uncertainty value of around ± 20 Gy on D90. PICT is a valuable technique but its accuracy and consistency limitations must be appreciated.